High Performance Leadership and Its Influence on Financial Growth in Indian Corporates - Shankaran Sumesh, Sangeeta (Digital Repository of Theses, 2025)
In today’s competitive era, there are umpteen challenges faced by corporate leaders in achieving their financial targets. The leaders are also held accountable and responsible for any drop in financial performance to the Board of Directors as well as to the shareholders of their organization. Every business seeks to grow at a fast pace and wants sustainable profits. Normally, the Chief Executive Officer (CEO) or the Managing Director (MD) alone is pulled up for the poor financial results. However, while the CEO / MD is the specific point of contact, they can deliver only when they have an efficient and capable leadership team to support them. This being the case, what capabilities will enable the leadership teams to contributing to improved financial performance of the business is the objective of this study. Therefore, embarking on this study to deep dive into the four main parameters of leadership capabilities which are leadership drive, leadership skills, leadership analytics and leadership impact. This is being achieved through a survey conducted on Indian corporate leaders and their reporting manager across various industries. The results of this study reveals interesting insights which is being coined as “Organizational Insights of Leadership (OIL)”. This reveals how the four parameters lead to high performance in leadership. It further reveals leadership expectation gaps within organizations’ which needs to be bridged in order to achieve the peak performance of the leadership team. The study also talks about ways and means to bridge this leadership expectation gap and further shares the necessary steps that can be taken by the leadership team to improve the financial performance of the business. To conclude, corporates need to work around growth strategies to develop leadership capabilities that will enhance the financial performance of the business. This will result not only in improved business performance leading to better financial results but also enable the leaders to feel good about themselves, their contribution to the business and result in higher efficiencies.